A Comparison of Physical Therapy Protocols Between Open Latarjet Coracoid Transfer and Arthroscopic Bankart Repair. (March 2020) - Beletsky, Alexander; Cancienne, Jourdan M.; Manderle, Brandon J.; Mehta, Nabil; Wilk, Kevin E.; Verma, Nikhil N.
Context: Recent studies examining return to sport after traumatic shoulder instability suggest faster return-to-sport time lines after bony stabilization when compared with soft tissue stabilization. The purpose of the current study was to define variability across online Latarjet rehabilitation protocols and to compare Latarjet with Bankart repair rehabilitation time lines. Evidence Acquisition: Online searches were utilized to identify publicly available rehabilitation protocols from Accreditation Council for Graduate Medical Education (ACGME)–accredited academic orthopaedic surgery programs. Study Design: Descriptive epidemiology study. Level of Evidence: Level 3. Results: Of the 183 ACGME-accredited orthopaedic programs reviewed, 14 institutions (7.65%) had publicly available rehabilitation protocols. A web-based search yielded 17 additional protocols from private sports medicine practices. Of the 31 protocols included, 31 (100%) recommended postoperative sling use and 26 (84%) recommended elbow, wrist, and hand range of motion exercises. Full passive forward flexion goals averaged 3.22 ± 2.38 weeks postoperatively, active range of motion began on average at 5.22 ± 1.28 weeks, and normal scapulothoracic motion by 9.26 ± 4.8 weeks postoperatively. Twenty (65%) protocols provided specific recommendations for return to nonoverhead sport–specific activities, beginning at an average of 17 ± 2.8 weeks postoperatively. This was compared with overhead sports or throwing activities, for which 18 (58%) of protocols recommended beginning at a similar average of 17.1 ± 3.3 weeks. Conclusion: Similar to Bankart repair protocols, Latarjet rehabilitation protocols contain a high degree of variability with regard to exercises and motion goal recommendations. However, many milestones and start dates occur earlier in Latarjet protocols when compared with Bankart-specific protocols. Consequently, variability in the timing of rehabilitation goals may contribute to earlier return to play metrics identified in the broader literature for the Latarjet procedure when compared with arthroscopic Bankart repair. Strength of Recommendation Taxonomy (SORT): Level C.